Sub-100-fs Ultrafast Fiber Laser Using Nonlinear Optical Fiber Systems: Perspectives and Challenges - Kuen Yao Lau; Meng Pang; Minglie Hu; Xiaofeng Liu; Nianqiang Li; Jianrong Qiu (Ultrafast Science)
Sub-100-fs ultrafast fiber lasers are crucial light sources for various practical applications. Generating these lasers directly from fiber laser oscillators remain an important yet challenging task. Here, a comprehensive review is conducted on 2 general approaches to generating sub-100-fs ultrafast fiber lasers using nonlinear optical fiber systems. First, pulse compression through the direct generation of laser pulses from a laser resonator was achieved by managing intracavity group velocity dispersion to be nearly zero. This was accomplished by generating stretched pulses using pairs of grating, prisms, or optical fibers. Furthermore, pulse compression was performed external to the laser resonator when intracavity pulse compression is difficult. In this approach, sub-100-fs ultrafast fiber lasers were achieved using pairs of grating or prism for dispersion compensation, fiber amplifiers, and chirped pulse amplification techniques to generate high-power laser pulses and optical fibers to achieve nonlinear spectral broadening. Subsequently, current challenges in achieving sub-100-fs ultrafast fiber lasers are discussed, along with perspectives on future developments. This review is expected to provide insights and simulate ideas for advancing sub-100-fs ultrafast fiber lasers using nonlinear optical fiber systems.